(untitled) (Docentes 2.0 Journal, 2013)
Practical knowledge is a distinctive characteristic of engineers. This relationship or impact that ICT has generated in the engineering world has helped to create, plan, implement, manage, evaluate and supervise information systems synergistically integrating organizations with the aim of improving their competitiveness.